“The Whole Island”. Literary space and intertextuality in Wide Sargasso Sea, by Jean Rhys - Goenaga Conde, Beatriz M. (2024)
The main objective of this article is aimed at assessing the functions of intertextuality in the construction of the Caribbean insular space in Wide Sargasso Sea, by the Dominican writer Jean Rhys. For this reason, it was analyzed the intertextual relations between Jane Eyre, by Charlotte Bronte and Wide Sargasso Sea, by Jean Rhys with emphasis on the island as an explicitly presented literary space. As a result, it was found that the main function of intertextuality in this text responds to the Calibanesque and demystifying intention of dismantling the archetypes in which the image of the other has been erected in the discourse of power. Likewise, the present analysis has made it possible to reveal the richness of the connotation granted in Wide Sargasso Sea to the island and its added meanings. This network of meanings reinforces its Caribbean cultural identity.